Deferensifikasi dan Diversifikasi Produk dalam Pengembangan Produk Tour BPW - Hari Rachmadi (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2008)
The meaning of diversification and diversification product is to make a product with kinds of various subject and another subject (tourism object). Facility or service so it looks all product has her own specialization the is a sport, cultural, and adventure so it makes more kinds of interesting product. The diversification and deferensification product is useful to increase service and sales tour package in a travel agent because that can make a change at tour package more variety and more interest. The methode is to fix up all of the components better. So the diversification and desertification product very important to the realization